Two new species of the genus Dischidia R. Br. (Asclepiadaceae) for the flora of Vietnam - Bach, Tran The; Phuong, Vu Xuan (Academia Journal of Biology, 2015)
Dischidia singularis Craib and D. griffithii Griff. ex Hook. f. (Dischidia R. Br., Asclepiadaceae) are two new records for the flora of Vietnam. D. singularis Craib and D. griffithii Griff. ex Hook. f. distinguish with the other species of Dischidia in Vietnam by: shape of corona; stem and leave glabrous; shape of leaves; hair on lobes; size of inflorescences; caudicles longer or shorter than corpuscle. D. singularis Craib distinguish with D. griffithii Griff. ex Hook. f. by: shape of leave; lobes of corolla hair; caudicles longer than corpuscle.